Annual report - Eurobodalla (N.S.W.). Council ([Moruya, N.S.W.] : Eurobodalla Shire Council, 2008)
Annual report of Eurobodalla Shire Council reporting on Council's financial, strategic and operating performance.
Description based on: 2008/09.
Title from title screen (viewed on 12 August 2010)
Report for year ended 30 June.
Available via World Wide Web. On 12/08/10 freely available from website of Eurobodalla Shire Council at: http://www.eurocoast.nsw.gov.au/publications.
System requirements: Adobe Acrobat Reader to access files in a PDF format.
Continues print version of publication.
Keywords: Eurobodalla (N.S.W.). -- Council -- Periodicals; Eurobodalla (N.S.W.) -- Periodicals